Revival of the mother-baby friendly initiative (MBFI) in South Africa: towards a quality improvement project - Welma Lubbe; Zandile Kubeka; Ann Behr; Gilbert Tshitaudzi; Sithembile Dlamini-Nqeketo; Jessica Botha (International Breastfeeding Journal, 2024)
Abstract Background The discontinuation of “Mother-Baby Friendly” accreditation, coupled with the impact of the COVID-19 pandemic, has contributed to reduced breastfeeding rates observed in parts of South Africa. Consequently, the Child, Youth and School Health cluster of the National Department of Health, with support from the World Health Organization and United Nations Children’s Fund, organised a Mother-Baby Friendly initiative revitalisation workshop. Methods Held in Johannesburg, South Africa, on June 29–30, 2022, the workshop brought together local and international breastfeeding promotion experts to engage on issues related to the revitalisation of the Mother-Baby Friendly Initiative. The workshop included presentations and group sessions aimed at setting expectations, evaluating the Ten Steps to Successful Breastfeeding, and developing actionable revitalisation strategies. Results Inadequate monitoring of the Mother-Baby Friendly Initiative implementation and adherence to the Ten Steps was identified as a major implementation bottleneck. Participants identified steps ten (coordinating discharge so that parents and their infants have timely access to ongoing support and care), five (supporting mothers to initiate and maintain breastfeeding and manage common difficulties), and two (ensuring that staff have sufficient knowledge, competence, and skills to support breastfeeding) of the Baby-Friendly Hospital Initiative as the most difficult to implement. Step seven (enabling mothers and their infants to remain together and to practise rooming-in 24 h a day) was the least difficult to implement. Workshop participants identified the following proposed solutions to revitalise breastfeeding promotion: strengthening capacity building and mentorship, improving monitoring and accountability measures, and certification of facilities meeting the initiative’s standards. Conclusion Current breastfeeding policies and practices must be evaluated by the National Department of Health in collaboration with provincial and private representatives of the initiative to effectively revitalise the Mother-Baby Friendly Initiative. Moreover, an integrative monitoring framework must be developed through stakeholder engagement, role clarification, and ownership. While collaboration between the private and public sectors is required to promote training and communication within healthcare facilities and communities.